Spontaneous variability and reactive postural beat-to-beat changes of integral ECG body surface potential maps - Kellerová, Eva; Szathmáry, Vavrinec; Kozmann, G; Haraszti, K; Tarjányi, Z (Physiological research, 2010)
There is virtually no information on spontaneous variability of ECG body surface potential maps (BSPMs) and on dynamics of their reactive changes in healthy subjects. This study evaluated quantitatively the depolarization (QRS) and repolarization (QRST) parameters derived from the respective integral BSPMs, constructed beat-to-beat, from continual body surface ECG records in 9 healthy men resting supine, during head-up tilting and sitting. Spontaneous variability of the BSPMs parameters, both at rest and during postural reactions, was characterized by significant respiratory and low frequency oscillations, more pronounced when related to repolarization. Head-up tilting and sitting-up evoked significant decrease in the QRST-BSPM amplitudes, widening of the angle ? and reduction of nondipolarity indexes, compared to the respective supine values. All these changes were gradual, characterized by transition phenomena and prolonged after-effects. Tilting back to horizontal restored the resting supine values. The postural effects on depolarization were individually more variable and in the average showed a minimal QRS-BSPM amplitude increase. Beat-to-beat analysis of a train of ECG BSPMs provided the first evidence of spontaneous, non-random, respiratory and low frequency oscillations of the ventricular repolarization pattern, and the first insight into the dynamics of body posture associated changes in ventricular recovery.
Keywords: elektrokardiografie; financování organizované; dospělí; srdeční frekvence; převodní systém srdeční; Financing, Organized; Heart Conduction System; lidé; postura těla; Humans; mužské pohlaví; mapování potenciálů tělesného povrchu; Male; Heart Rate; Posture; Adult; Body Surface Potential Mapping; Electrocardiography